Development of Processed Coconut Products (Cocos nucifera L) in the Form of Coconut Chips in Togafo Village, North Ternate City - Dewi, Eka Kusuma (Altifani Journal: International Journal of Community Engagement, 2021)
Community service is an activity that aims to help certain communities in several activities without expecting any form of reward. This community service is focused on processing coconut plantation products (Cocos nucifera .L), which is one of the main plantation products around the service area. Service activities were carried out for the community in Togafo Village, North Ternate City. This training is expected to be able to help increase people's sources of income and increase public knowledge about how to process food from coconut raw materials. The method of activity is carried out by the tutorial method and joint practice. During the training, the participants enthusiastically participated in the activities and actively engaged in two-way discussions. Participants understand and can practice coconut processing techniques into coconut chips, and this can be a business opportunity.